Extended Lapped Transforms: Properties, Applications, and Fast Algorithms - Malvar, Henrique S.; Malvar, Henrique S. (IEEE Transactions in Acoustics, Speech, and Signal Processing, 1992)
The family of lapped orthogonal transforms is extended to include basis functions of arbitrary length. Within this new family, the extended lapped transform (ELT) is introduced, as a generalization of the previously reported modulated lapped transform (MLT). Design techniques and fast algorithms for the ELT are presented, as well as examples that demonstrate the good performance of the ELT in signal coding applications. Therefore, the ELT is a promising substitute for traditional block transforms in transform coding systems, and also a good substitute for less efficient filter banks in subband coding systems.